Full characterization and cytotoxic activity of new silver(i) and copper(i) helicates with quaterpyridine. (5th August 2016) - Adamski, Ariel; Fik, Marta A.; Kubicki, Maciej; Hnatejko, Zbigniew; Gurda, Dorota; Fedoruk-Wyszomirska, Agnieszka; Wyszko, Eliza; Kruszka, Dariusz; Dutkiewicz, Zbigniew; Patroniak, Violetta
Abstract : DNA binding and cells' cycle disorders caused by four new dinuclear Ag(i ) and Cu(i ) double helicates with quaterpyridine ligands. Abstract : The self-assembly of 6, 6′′′′-dimethyl-2, 2′;6′, 2′′;6′′, 2′′′-quaterpyridineL with tetrahedral ions of silver(i ) and copper(i ) leads to the formation of dinuclear double stranded helicates1–4 . 1 H NMR studies confirm the stability of each helicate both in 2% aqueous DMSO solution, which plays the role of a medium in biological studies, and in the cell extract solution. The cytotoxic properties of complexes were examined on two cancerous cell lines: HeLa and T-47D as well as on the non-neoplastic fibroblasts HaCaT by using the MTT assay method. The IC50 values of cisplatin towards cancerous cell lines are rather comparable. However, the trend of cancerous/healthy cell selectivity is not maintained. One may assume a different mechanism of action. Moreover, it is possible to distinguish the cell death pathway triggered by Ag(i ) and Cu(i ) helicates presented in this study. Flow cytometry, EtBr displacement titrations, CD titrations, DNA melting experiments and DFT calculations were used to characterize the type of interaction and the mechanism of cytotoxic action.